Differences in the influence of Direct Instruction and Demonstration in Volleyball Games for Elementary Madrasah Students on Student Learning Motivation - Sarifudin, Sarfudin; Ginanjar, Agi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to test the effect of the Direct Instruction (DI) model and demonstration on the learning motivation of elementary school students and to test the differences in the effect of the DI model and demonstration on the learning motivation of elementary school students. The research method uses an experiment with nonequivalent control group design. Participants were 56 students of Madrasah Ibtidaiyah Miftahul Huda Sukadana. The research instrument used a learning motivation questionnaire in physical education for elementary school students. Data analysis techniques used statistical descriptions, paired sample t-tests, and independent samples t-tests. The results of the study concluded that there was an influence of the DI and demonstration models on the learning motivation of students of Madrasah Ibtidaiyah and there was a difference in the influence of the DI and demonstration models on the learning motivation of students of Madrasah Ibtidaiyah seen from the average difference. Recommendations for teachers or instructors that the selection of a model greatly influences the learning motivation of students in participating in volleyball learning. Thus, students who have high motivation can develop and improve the quality of education itself, especially in volleyball sports.